2016
DOI: 10.3390/ijms17081237
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and FGF2 Improve Revascularization, Survival, and Oocyte Quality of Cryopreserved, Subcutaneously-Transplanted Mouse Ovarian Tissues

Abstract: This study was conducted to investigate the effect of the vascular endothelial growth factor (VEGF) and fibroblast growth factor 2 (FGF2) on revascularization, survival, and oocyte quality of cryopreserved, subcutaneously-transplanted mouse ovarian tissue. Autologous subcutaneous transplantation of vitrified-thawed mouse ovarian tissues treated with (experimental group) or without (control group) VEGF and FGF2 was performed. After transplantation to the inguinal region for two or three weeks, graft survival, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
(50 reference statements)
1
29
1
Order By: Relevance
“…Several studies reported the positive effects of bFGF on angiogenesis and follicular survival in autograft and xenograft models, even though the total dose of bFGF (100–150 ng/mL for in vitro pretreatment, total 90–750 ng for in vivo administration via subcutaneous injection of free form or local transplantation with ovarian tissues using fibrin hydrogel or basement membrane extract) was much lower in these studies than in the present study (total 100 μg). However, it was not clear what was the actual dosage of active form of bFGF in vivo because there was no information about the in vivo release of bFGF.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Several studies reported the positive effects of bFGF on angiogenesis and follicular survival in autograft and xenograft models, even though the total dose of bFGF (100–150 ng/mL for in vitro pretreatment, total 90–750 ng for in vivo administration via subcutaneous injection of free form or local transplantation with ovarian tissues using fibrin hydrogel or basement membrane extract) was much lower in these studies than in the present study (total 100 μg). However, it was not clear what was the actual dosage of active form of bFGF in vivo because there was no information about the in vivo release of bFGF.…”
Section: Discussioncontrasting
confidence: 77%
“…Recently, various angiogenic growth factors have been evaluated for inducing neovascularization of fresh and frozen‐thawed ovarian grafts in autograft and xenograft animal models. Basic fibroblast growth factor (bFGF), which is one of the major regulators of angiogenesis, plays important roles not only in new vessel formation, but also in the modulation of vascular epithelial growth factor (VEGF) expression and upregulation of both FGF and VEGF receptors .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to mediation of endothelial cells angiogenic process, studies with human ovarian microvascular endothelial cells (hOMECs) proved that VEGFA promote endothelial cell migration [7]. Li et al (2016) indicate improved quality and survival rate of subcutaneously-transplanted mouse ovarian tissue in VEGF coupled with FGF2-treated subjects [8]. Furthermore, IVM of bovine oocytes supplemented with VEGF results in an improvement of cytoplasmic maturation, with a positive impact on oocyte developmental capacity [9].…”
Section: Discussionmentioning
confidence: 99%
“…The exact half-life of VEGF 164 used in this study is not known, but VEGF is known to have short half-life [ 34 ]. Even though VEGF has short half-life, it shows its angiogenic effect in previous studies [ 35 37 ]. Since the half-life of Ang-2 seems longer than that of VEGF, injection timing before XT was determined based on the half-life of Ang-2 being 18 hours, and the angiogenic factors were injected once again before the XT procedures.…”
Section: Discussionmentioning
confidence: 98%